Pericentric inversion inv(7)(p11q21.1): report on two cases and genotype-phenotype correlations - Vorsanova, S.G.; Iourov, I.Y.; Demidova, I.A.; Kolotii, A.D.; Soloviev, I.V.; Yurov, Y.B. (Цитология и генетика, 2006)
We report on two unrelated cases of pericentric inversion 46,XY,inv(7)(p11q21.1) associated with distinct pattern of malformation including mental retardation, development delay, ectrodactyly, facial dismorphism, high arched palate. Additionally, one case was found to be characterized by mesodermal dysplasia. Cytogenetic analysis of the families indicated that one case was a paternally inherited inversion whereas another case was a maternally inherited one. Molecular cytogenetic studies have shown paternal inversion to have a breakpoint within centromeric heterochromatin being the cause of alphoid DNA loss. Maternal inversion was also associated with a breakpoint within centromeric heterochromatin as well as inverted euchromatic chromosome region flanked by two disrupted alphoid DNA blocks.